A Chinese pediatric patient with thalassemia traits and compound heterozygous mutations in the PIEZO1 gene suspected of having dehydrated hereditary stomatocytosis - Weijie Chen; Xinyu Li; Huaqing Yang; Chao Niu; Yushan Huang; Lang Qin; Mingyan Fang; Shaofen Lin; Kaimei Wang; Yuan Zhuang; Yuhua Ye; Xin Jin; et al. (Hematology)
Background Dehydrated Hereditary Stomatocytosis (DHS), also known as Hereditary Xerocytosis (HX), is a rare genetic disorder primarily arising from gain-of-function mutations in PIEZO1, which disrupt mechanosensitive ion channels on red blood cell membranes. This dysfunction leads to cellular dehydration and chronic anemia, while DHS/HX cells exhibit increased hypotonic resistance. Interpreting PIEZO1 variants requires integrating clinical findings with specialized knowledge.Methods Laboratory tests, whole-genome sequencing, and Sanger sequencing were conducted for clinical phenotyping and identification of disease-causing mutations within the proband and his parents.Results The proband was found to have both β-thalassemia trait and Dehydrated Hereditary Stomatocytosis. The proband inherited compound heterozygous mutations in the PIEZO1 gene (c.136G > A and c.6307C > G) from his mother and father, respectively. Additionally, the proband had a heterozygous β-globin gene mutation (c.315 + 2delT) inherited from his father.Conclusion Compared to patients with either DHS/HX or β-thalassemia alone, this patient, as a β-thalassemia carrier with suspected Dehydrated Hereditary Stomatocytosis, exhibited highly complex laboratory findings. Genetic testing played a crucial role in diagnosing conditions with overlapping clinical features. Given the increased risk of thromboembolic complications, splenectomy is contraindicated in DHS/HX patients, highlighting the necessity for precise diagnosis of DHS/HX and molecular confirmation of suspected hereditary red blood cell disorders.